Examining the correlation between phubbing and life satisfaction in adults during covid-19 pandemic - Polat, Filiz; Karasu, Fatma (Journal of Dependence, 2022)
Objective: This study was carried out to investigate the correlation between the phubbing and life satisfaction in adult individuals in Turkey during the pandemic. Method: The population of this descriptive study was composed of individuals over the age of 18 in Turkey. The study was carried out with 682 individuals between 15.02.2021 and 15.03.2021 by using the snowball sampling method, one of the improbable sampling methods. The data were collected using “Personal Information Form, Phubbing Scale, and Satisfaction With Life Scale”. Results: A negative and moderate correlation was found between Phubbing Scale and Satisfaction With Life Scale. It was determined that the phubbing levels of the participants were moderate and their life satisfaction were low. Conclusion:A significant correlation was found between phubbing and life satisfaction. Nurses should provide individuals with positive health behaviors to prevent phone addiction during the covid-19 pandemic process.